2015
DOI: 10.1111/obr.12306
|View full text |Cite
|
Sign up to set email alerts
|

Windows of opportunity for physical activity in the prevention of obesity

Abstract: Tackling increasing rates of obesity is likely to be a defining feature of health care over the next several decades. Adult obesity is a persistent and treatment-resistant problem. Consequently, an emerging theme in the literature is to commence prevention efforts earlier in the developmental time course. This view is based primarily on epidemiological data demonstrating a link between traits manifesting early during development and increased obesity risk in adulthood. Physical activity is a perennial factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 144 publications
0
17
0
1
Order By: Relevance
“…It has been proposed that early-life exercise training is a positive stimulus for reprogramming offspring exposed to detrimental insults in utero, such as placental restriction (Laker et al 2011;Laker et al 2012;Gatford et al 2014;Street et al 2015). We found that exercise training early in life in rats (from 5 to 9 weeks of age only, treadmill running) normalized the 50% lower relative islet surface area and β-cell mass in adulthood in rats born small for gestational age (Laker et al 2011).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…It has been proposed that early-life exercise training is a positive stimulus for reprogramming offspring exposed to detrimental insults in utero, such as placental restriction (Laker et al 2011;Laker et al 2012;Gatford et al 2014;Street et al 2015). We found that exercise training early in life in rats (from 5 to 9 weeks of age only, treadmill running) normalized the 50% lower relative islet surface area and β-cell mass in adulthood in rats born small for gestational age (Laker et al 2011).…”
Section: Introductionmentioning
confidence: 59%
“…; Street et al . ). We found that exercise training early in life in rats (from 5 to 9 weeks of age only, treadmill running) normalized the 50% lower relative islet surface area and β‐cell mass in adulthood in rats born small for gestational age (Laker et al .…”
Section: Introductionmentioning
confidence: 97%
“…Children who participate in regular physical activity typically have higher levels of cardiorespiratory fitness, stronger muscles and bones, lower body fatness, less prevalence of chronic diseases, and reduced symptoms of anxiety and depression . Additionally, children who are physically active are more likely to become active adults, and this may mitigate obesity risk later in life …”
mentioning
confidence: 99%
“…Insufficient physical activity (PA) levels and obesity are issues of considerable concern in modern society [1]. The prevalence of obesity in adults is up to 40% in the USA [2] and up to 47.6% in Europe [3].…”
Section: Introductionmentioning
confidence: 99%